(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Teachers’ professional development can be defined as those processes and activities designed to enhance the professional knowledge, skills, and attitudes of educators so that they might, in turn, improve the learning of students.